2012
DOI: 10.1136/bmj.e440
|View full text |Cite
|
Sign up to set email alerts
|

How much of a social media profile can doctors have?

Abstract: Social media have made it harder to maintain a distinction between professional and personal lives. Margaret McCartney looks at the dangers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 1 publication
1
29
0
Order By: Relevance
“…Privacy and confidentiality associated concerns of patients and colleagues should be addressed strictly. [8]Online contact with patients breaching doctor–patient relationship may be professionally inappropriate. A survey of residents and fellows revealed that 85% declined patients' “friend” requests.…”
Section: Constraints and Hazards Of Social Network Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Privacy and confidentiality associated concerns of patients and colleagues should be addressed strictly. [8]Online contact with patients breaching doctor–patient relationship may be professionally inappropriate. A survey of residents and fellows revealed that 85% declined patients' “friend” requests.…”
Section: Constraints and Hazards Of Social Network Sitesmentioning
confidence: 99%
“…Privacy and confidentiality associated concerns of patients and colleagues should be addressed strictly. [8]…”
Section: Constraints and Hazards Of Social Network Sitesmentioning
confidence: 99%
“…It has been suggested that one effect of the undoing of the medical 'God complex' has been to humanize medicine and populate it with doctors who are fallible but professional." 9 Perhaps a good rule of thumb is that we should make sure that our conduct at all times justifies our patients' trust in us and the public's trust in the profession. 9 Guide to creating and maintaining a "digital footprint" Taking the "social media plunge" can have consequences regarding one's exposure and digital persona.…”
Section: The Code Of Medical Ethicsmentioning
confidence: 99%
“…9 Perhaps a good rule of thumb is that we should make sure that our conduct at all times justifies our patients' trust in us and the public's trust in the profession. 9 Guide to creating and maintaining a "digital footprint" Taking the "social media plunge" can have consequences regarding one's exposure and digital persona. Following are some recommendations:…”
Section: The Code Of Medical Ethicsmentioning
confidence: 99%
“…There have been cases of unethical conduct [22] which have led regulatory authorities such as the General Medical Council (GMC) a and the American Medical Association (AMA) b to establish specific guidance for the use of social media by doctors…”
mentioning
confidence: 99%